OTOMATISASI SIRKULASI AIR PADA INSTALASI AQUAPONIK DENGAN PANEL SURYA (SOLAR CELL) SEBAGAI SUMBER ENERGI ALTERNATIF - Fifin Hindarti (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2018)
New and Renewable energy is not only an alternative energy that can meet increasing energy needs, but also green energy that does not cause harmful effects on humans and the environment such as energy derived from fossils. The application of solar cells as a source of electrical energy to modern agricultural systems, especially the aquaponics system is one of the efforts to develop new and renewable energy that is environmentally friendly. This research is a technological innovation that can cover the weaknesses of aquaponic systems in general by using solar panels to convert solar energy into electrical energy and equipped with water circulation automation technology so that the water needs are always guaranteed. The design of automatic water circulation regulator hydroponic planting method uses a timer as an automatic, solar panels as energy converters, solar charge controller as a regulator of electric current balance. The implementation of this research consists of several stages, namely: the initial data collection stage, the system development stage, and the research data collection stage. The results showed that the water pump in the aquaponic fish pond on the first, second and third days showed that the water pump was 12 V and the average flow of the fish pond water pump was 1.15 A. The data also showed that The highest measurement carried out for 3 days resulted in an average voltage of 12.68 V and a current of around 1.75 A, and the lowest measurement produced an average voltage of 12.42 V and a current of around 1.63 A. Based on the data in the study this, solar panels with a large 50 wp can meet the load requirements (water pump) to operate so that they can help circulate water in aquaponic installations.